Fatal Airway Obstruction in a Man With a Cystic Hygroma. (September 2018) - Wygant, Cassandra Maria; Cohle, Stephen D.
Abstract : Abstract: We describe a 24-year-old man with a cystic hygroma of the left side of the lower neck that led to sudden death. Cystic hygroma (cystic lymphangioma) is a congenital malformation of the lymphatic system. The patient, who had a tracheostomy because of airway obstruction from the cystic hygroma, was found dead with his tracheostomy tube on the floor next to him. Complications of cystic hygroma include infiltration of the neck causing airway obstruction, dysphagia, pain, and obstructive sleep apnea.